Post-Vaccination Immunity to Pertussis in Children of Lipetsk, New Management Capabilitiesto Infection - T. V. Timofeeva; E. G. Googe; N. M. Fatina (Эпидемиология и вакцинопрофилактика, 2019)
Relevance. In the structure of the incidence of controlled infections in the Russian Federation, whooping cough takes one of the leading places, and in 2018 there is a two-fold increase in the incidence compared with 2017.The aim. Determination of the level of postvaccination immunity to pertussis infection in children of Lipetsk aged 3 to 10 years and assessment of the safety of booster vaccination with a combination vaccine against diphtheria and tetanus with acellular pertussis.Materials and methods. Analysis of the incidence of pertussis and the quality of vaccine prevention according to planned seromonitoring in Lipetsk (2017). 100 patients were vaccinated with a booster dose of Adaсel. The study tested reactogenicity and safety of the vaccine.Results. There is a relationship between the epidemic process of whooping cough and the short duration of post-vaccination immunity. Epidemiology of whooping cough dictates the need to change the tactics of vaccination, the introduction of repeated revaccination of children and adults using cell-free vaccines.Conclusions The data obtained confirm the safety and good tolerability of the Adacel vaccine in clinical practice.